HUBUNGAN INTERAKSI SOSIAL DENGAN KUALITAS HIDUP PENDERITA KUSTA - Lutfi Wahyuni (Jurnal Keperawatan, 2016)
Social interaction is the key of all social life, therefore it is not possible to the needs of social could have been met without any social interaction. If the social disorder, an individual would feel the decline in the quality of life to himself. Good quality of life become more important for patients with kusta, given the difficulty of achieving health and treatments can take a long time. This research aims to understand the relation between social interaction with the quality of life of patients with kusta. A design research that is used correlational analytic. Approach used was cross sectional. The population research that was all of the adult patients with kusta in the work area Rs Kusta Sumber GlagahMojokerto Regency. The samples used in research that is saturated samples with 27 of respondents. The collection of data using a questionnaire and processed in editing, coding, scoring, and then tabulating, after that will be presented in table form a frequency distribution. The results of research shows that most respondents have interaction less than good and low quality of life as many as 12 respondents ( 75,0 % ), this show that there is the relationship between social interaction and quality of life of patients with kusta. Social interaction less good can be due to environmental factors for fear that keeps patients infected with kusta.